Brodalumab, a human anti-interleukin-17-receptor antibody in the treatment of Japanese patients with moderate-to-severe plaque psoriasis: Efficacy and safety results from a phase II randomized controlled study. Issue 1 (January 2016) - Nakagawa, Hidemi; Niiro, Hiroaki; Ootaki, Kenji
Highlights: Psoriasis is a chronic inflammatory immune-mediated skin disease. Excessive IL-17 signaling is thought to contribute to the pathogenesis of psoriasis. Brodalumab is a human anti-IL-17 receptor A monoclonal antibody. Brodalumab demonstrated rapid and robust improvements in clinical outcomes in Japanese patients with moderate-to-severe plaque psoriasis. Safety profile was acceptable in the phase 2 study. Abstract: Background: Brodalumab (KHK4827 or AMG 827) is a human monoclonal antibody that binds to the human interleukin (IL)-17 receptor A and blocks the biological activities of IL-17A, IL-17F, IL-17A/F, and IL-17E also known as IL-25. A 12-week phase 2 trial in the USA, Europe, and other countries showed the good efficacy of brodalumab in treating patients with moderate to severe plaque psoriasis. However, with the exception of a phase 1 study, a clinical trial of brodalumab in psoriasis has not been undertaken in Japan. Objective: To evaluate the efficacy and safety of brodalumab in Japanese patients with moderate-to-severe plaque psoriasis, including psoriatic arthritis, in a multicenter, randomized, double-blind, placebo-controlled, parallel-group comparative phase 2 study, and to assess the pharmacokinetics of brodalumab. Methods: Japanese patients with moderate-to-severe plaque psoriasis, including psoriatic arthritis, were randomized to receive 70 mg, 140 mg, or 210 mg of brodalumab, or placebo, injected subcutaneously at baseline and weeks 1, 2, 4, 6, 8, and 10. The primary efficacy endpoint was the percentage improvement in the Psoriasis Area and Severity Index (PASI) score from baseline to week 12. Secondary efficacy endpoints included the percentage of patients with ≥75% reduction of PASI scores (PASI 75), ≥90% (PASI 90), and 100% (PASI 100) and the percentage of patients with a static physician's global assessment (sPGA) of 0 (clear) or 1 (almost clear) at week 12. Safety was evaluated by assessing the adverse events (AE) and the patients' hematologic and laboratory values. Results: At week 12, the mean percentage improvements in the PASI scores were 37.7%, 82.2%, 96.8%, and 9.4% in the 70 mg, 140 mg, 210 mg, and placebo groups, respectively, ( p  < 0.001 for all comparisons with placebo). The percentage of patients with PASI 75, PASI 90, and PASI 100 at week 12 were 7.9%, 2.6%, and 0%, respectively, in the placebo group, 25.6%, 15.4%, and 2.6%, respectively, in the 70 mg brodalumab group, 78.4%, 64.9%, and 35.1%, respectively, in the 140 mg brodalumab group, and 94.6%, 91.9%, and 59.5%, respectively, in the 210 mg brodalumab group. Concerning psoriatic arthritis, at week 12, the numbers (%) of patients fulfilling the American College of Rheumatology response criteria for a 20% improvement were 0 (0%) in the placebo group, and 1 (20%), 2 (40%), and 4 (100%) in the 70 mg, 140 mg, and 210 mg brodalumab groups, respectively. The percentages of patients with Dermatology Life Quality Index scores of 0 or 1 at week 12 were greater in the 140 mg (54.1%) and the 210 mg (56.8%) brodalumab groups than in the placebo group (8.8%). The most common AE in the brodalumab groups were nasopharyngitis (12.4% vs. 7.9% for placebo), diarrhea (5.3% vs. 0%), upper respiratory tract inflammation (3.5% vs. 0%), and folliculitis (3.5% vs. 0%). Conclusion: The rapid, robust efficacy of brodalumab and its favorable safety profile shown in the current study confirm previous studies conducted in Caucasian people, further warranting the use of brodalumab as a new treatment option for plaque psoriasis.